Does scale matter in community bank performance? Evidence obtained by applying several new measures of performance - Joseph P. Hughes; Julapa Jagtiani; Loretta J. Mester; Choon-Geol Moon (Rutgers University, Department of Economics, 2019)
We consider how size matters for banks in three size groups: small community banks with assets less than 1 billion, large community banks with assets between 1 billion and 10 billion, and midsize banks with assets between 10 billion and 50 billion. To illustrate the differences between these banks and larger banks whose business models are distinctly different, we examine large banks with assets between 50 billion and 250 billion and the largest banks with assets exceeding 250 billion. Community banks have potential advantages in relationship lending compared with large banks. However, increases in regulatory compliance and technological burdens may have disproportionately increased community banks' costs, raising concerns about small businesses' access to credit. Our evidence suggests several patterns: (1) while small community banks exhibit relatively more valuable investment opportunities, larger community banks, midsize banks, and larger banks exploit theirs more efficiently and achieve better financial performance; (2) average operating costs that include costs related to regulatory compliance and technology decrease with size; (3) unlike small community banks, large community banks have financial incentives to increase lending to small businesses; and (4) for business lending and commercial real estate lending, compared with small community banks, large community banks, midsize banks, and larger banks assume higher inherent credit risk and exhibit more efficient lending. Thus, concern that small business lending would be adversely affected if small community banks find it beneficial to increase their scale is not supported by our results.
Keywords: G21; L25; 330; community banking; scale; financial performance; small business lending